PENGUATAN IDENTITAS LOKAL KERAJINAN SARUNG LAWO KEMBO SEBAGAI SUMBER EKONOMI RUMAH TANGGA - Damianus Tola; Sayful Amrin; Alina Indriani Beri; Dewi Seda Gadi4 (Bajang Institute, 2026)
This community service aims to strengthen the identity of the ndona community through household handicraft enterprises, specifically the production of sarung lawo kembo, as a from of creative expression rooted in the local wisdom of Manulondo village. Through these home based industries, both economic and cultural values embedded in the meanings and symbols represented in the motifs of the sarung lawo kembo can be identified and developed as a consumer attraction. Sarung lawo kembo is a traditional ikon weaving of the Ndona community, which holds high philosophical value and serves as a symbol of brotherhood, togetherness, and the social identity of the people. The results of the progam indicate that the household handicraft enterprixe of sarung lawo kembo represents a highly remarkable traditional of the ndona community. There are three types of lawo kembo motifs, namely lawo kabhi, lawo onemesa and lawo ngera. Each of these motifs carries distinct narratives and meanings within the social life the community. The preservation of sarung lawo kembo not only plays a role in maintain tradition, but also creates opportunities for the development of the creative emocomy among the ndona people. Furthermore it contributes to sustaining production community and strengthening the position of sarung lawo kembo as a cultural identity of the ndona community.